New insight into Salpa thompsoni distribution via glider-borne acoustics - Hann, Ashley M.; Bernard, Kim S.; Kohut, Josh; Oliver, Matthew J.; Statscewich, Hank (Frontiers in Marine Science, 2023)
Salpa thompsoni is an ephemerally abundant pelagic tunicate in the waters of the Southern Ocean that makes significant contributions to carbon flux and nutrient recycling in the region. While S. thompsoni, hereafter referred to as “salps”, was historically described as a polar-temperate species with a latitudinal range of 40 – 60°S, observations of salps in coastal waters of the Western Antarctic Peninsula have become more common in the last 50 years. There is a need to better understand the variability in salp densities and vertical distribution patterns in Antarctic waters to improve predictions of their contribution to the global carbon cycle. We used acoustic data obtained from an echosounder mounted to an autonomous underwater Slocum glider to investigate the anomalously high densities of salps observed in Palmer Deep Canyon, at the Western Antarctic Peninsula, in the austral summer of 2020. Acoustic measurements of salps were made synchronously with temperature and salinity recordings (all made on the glider downcasts), and asynchronously with chlorophyll-a measurements (made on the glider upcasts and matched to salp measurements by profile) across the depth of the water column near Palmer Deep Canyon for 60 days. Using this approach, we collected high-resolution data on the vertical and temporal distributions of salps, their association with key water masses, their diel vertical migration patterns, and their correlation with chlorophyll-a. While salps were recorded throughout the water column, they were most prevalent in Antarctic Surface Water. A peak in vertical distribution was detected from 0 – 50 m regardless of time of day or point in the summer season. We found salps did not undergo diel vertical migration in the early season, but following the breakdown of the remnant Winter Water layer in late January, marginal diel vertical migration was initiated and sustained through to the end of our study. There was a significant, positive correlation between salp densities and chlorophyll-a. To our knowledge, this is the first high resolution assessment of salp spatial (on the vertical) and temporal distributions in the Southern Ocean as well as the first to use glider-borne acoustics to assess salps in situ.